Colorectal cancer – applying a gender lens - Oberoi, Devesh; Jiwa, Moyez; McManus, Alexandra; Hodder, R. (Radcliffe Medical Press Ltd., 2014)
Background: Colorectal cancer (CRC) is a major global health problem with survival varying according to stage at diagnosis. The incidence of CRC is much higher in patients with lower bowel symptoms. The symptoms are non-specific and are commonly experienced in the general population. Biological and environmental factors account for the high incidence and poor prognosis of CRC in men.Objective: To review the behavioural factors influencing patient delay in seeking help for lower bowel symptoms using a gender lens.Methods: An extensive literature search was performed using various databases including Medline, PubMed, CINAHL Plus, EMBASE and PsycINFO (1993–2013). Various search terms including rectal bleeding, prevalence, colorectal cancer, consultation, help-seeking, gender differences and men were used. A systematic methodology including systematic data extraction and narrative synthesis was applied.Results: Thirty-two studies were included in the review. All studies except four were quantitative. Although there is some evidence that men delay more compared with women, there has not been any major improvement in the help-seeking behaviour for such symptoms over the past two decades. Several behavioural and demographic factors were associated with low rates of help-seeking.Conclusion: There are limited studies focusing on men's help-seeking behaviour for lower bowel symptoms. To facilitate timely help-seeking in men, it is important to understand their patterns of helpseeking for such symptoms. Further research to understand men's help-seeking behaviour is warranted.